New candidate radio supernova remnants detected in the GLEAM survey over 345° < l < 60°, 180° < l < 240°. (2019) - Hurley-Walker, N.; Filipović, M. D.; Gaensler, B. M.; Leahy, D. A.; Hancock, P. J.; Franzen, T. M. O.; Offringa, A. R.; Callingham, J. R.; Hindson, L.; Wu, C.; Bell, M. E.; For, B.-Q.; et al.
Abstract: We have detected 27 new supernova remnants (SNRs) using a new data release of the GLEAM survey from the Murchison Widefield Array telescope, including the lowest surface brightness SNR ever detected, G 0.1 – 9.7. Our method uses spectral fitting to the radio continuum to derive spectral indices for 26/27 candidates, and our low-frequency observations probe a steeper spectrum population than previously discovered. None of the candidates have coincident WISE mid-IR emission, further showing that the emission is non-thermal. Using pulsar associations we derive physical properties for six candidate SNRs, finding G 0.1 – 9.7 may be younger than 10 kyr. Sixty per cent of the candidates subtend areas larger than 0.2 deg 2 on the sky, compared to < 25% of previously detected SNRs. We also make the first detection of two SNRs in the Galactic longitude range 220°–240°.